2012
DOI: 10.1039/c2lc21247a
|View full text |Cite
|
Sign up to set email alerts
|

Digital LAMP in a sample self-digitization (SD) chip

Abstract: This paper describes the realization of digital loop-mediated DNA amplification (dLAMP) in a sample self-digitization (SD) chip. Digital DNA amplification has become an attractive technique to quantify absolute concentrations of DNA in a sample. While digital polymerase chain reaction is still the most widespread implementation, its use in resource—limited settings is impeded by the need for thermal cycling and robust temperature control. In such situations, isothermal protocols that can amplify DNA or RNA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 32 publications
4
156
0
Order By: Relevance
“…They demonstrated accurate quantification of relative and absolute DNA concentrations using digital loop-mediated DNA amplification (dLAMP) [94]. It is an inexpensive and easy-to-operate device for DNA amplification.…”
Section: Nucleic Acid Analysismentioning
confidence: 99%
“…They demonstrated accurate quantification of relative and absolute DNA concentrations using digital loop-mediated DNA amplification (dLAMP) [94]. It is an inexpensive and easy-to-operate device for DNA amplification.…”
Section: Nucleic Acid Analysismentioning
confidence: 99%
“…Following amplification and counting of number of compartments showed positive amplification result reveals the initial number of the targeted molecules in the sample allowing quantitative analysis of ultimate precision and accuracy [85]. This compartmentalization can be realized in form of water in oil emulsion [86,87] where each water droplet is considered as unique and independent reaction volume; or by distribution of the reaction mixture across hundreds and thousands of individual microfluidic vessels [88][89][90]. The approach was successfully shown both for PCR [87,88,91,92] and isothermal amplification techniques (LAMP) [89].…”
Section: Microfluidic Arraysmentioning
confidence: 99%
“…This compartmentalization can be realized in form of water in oil emulsion [86,87] where each water droplet is considered as unique and independent reaction volume; or by distribution of the reaction mixture across hundreds and thousands of individual microfluidic vessels [88][89][90]. The approach was successfully shown both for PCR [87,88,91,92] and isothermal amplification techniques (LAMP) [89]. Zhang et al [90] showed implementation of the microfluidic arrays full cycle of nucleic acids analysis including DNA/RNA extraction and their real-time amplification (Fig.…”
Section: Microfluidic Arraysmentioning
confidence: 99%
“…Additionally, such actuation methods are vulnerable to bubble formation and not suitable to load up dead-end structures that are attractive for quantitative digitized and multiplexed assays. [12][13][14] Most of the passive fluidic actuation methods lack effective positive control method or actuation reproducibility. [15][16][17][18][19] Take degas-driven flow as an example, it takes advantage of the Polydimethylsiloxane (PDMS) material to overcome the undesired bubble formation and enclosed chamber loading issue; however, it does not support a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%